Effects of rice importation on rice farming profitability in the municipality of Cabatuan, Iloilo - Alviar, Marlene Y.
The study was conducted primarily to determine the effects of rice importation on rice farming profitability. Specifically, it aimed to obtain information on farmer's perceptions on rice importation and its effects on the rice industry and to assess their corresponding alternatives and options. One hundred one sample farmers in Cabatuan, Iloilo were interviewed for the sources of data and information needed. Study findings were presented through simple descriptive statistics. The test of independence or Chi-square test was employed to establish relationship between selected variables.The study reveals that rice farming, which is a major source of income among sample farmers, remain unprofitable. Production costs are contingent on the following major production constraints identified by the farmers : a)water sources/irrigation; b) high costs of farm inputs and pesticides; c) pests and diseases; d0 climatological variability; and e) low farm gate prices of palay. With the advent of rice tradeliberalization, inflow of low-priced from other countries would put the farmers at a disadvantage. Local production may fall and rice farm areas could decrease. Results of the study reveal majority of the farmers (77%) would shift to some other alternatives in the event that imported rice competes with the local produce. More than one half would consider planting other crops specially vegetables, one third would raise hogs and chicken and the rest would engage in off-farm activities. Farmers who have no alternatives would still plant rice in the absence of other options available.Among the variables statistically tested for relationship on their eventual decisions on whether to plant non-rice crops, the source of household income apparently showed a significant influence on their decision; farmers whose major sources of income come from rice farming would probably not shift to other crops farming.Further, data reveals that there are no alternative sources of income for most of the farmers. Their skills are limited only to rice farming, and rice farms are not suited to growing other profitable crops. The farmers rest their hope on government support on irrigation/water sources and subsidy on farm inputs. The challenge lies on the government, its implementing units and concerned groups on how to simultaneously increase profitability in the farm and increase productivity of labor.